Division of Salary on Civil Servant Divorce Reviewed in Islamic Law Perspective - Nelhendra, Yusra (KIPS Institute Bukittinggi, 2026)
This study examines the legal consequences of divorce for male civil servants based on Article 8 of Government Regulation No. 45 of 1990, which amended Government Regulation No. 10 of 1983. The regulation requires male civil servants who divorce their wives to give part of their salary to their ex-wives until they remarry. This obligation differs from Islamic law and the Compilation of Islamic Law (KHI), which limits the financial obligations of husbands after divorce to alimony during the iddah period and the provision of mut'ah. This study aims to analyze the compatibility of Article 8 with the principles of Islamic law and evaluate the impact of its implementation on divorced male civil servants. The researcher used a qualitative library research method by reviewing relevant literature, legislation, and legal documents related to divorce and post-divorce obligations. The researcher analyzed the collected data using normative legal analysis. The results of the study indicate that the obligation to distribute a portion of male civil servants' salaries to their ex-wives until they remarry is contrary to Islamic law. However, this regulation serves as a legal protection mechanism for divorced women and as a disciplinary measure for civil servants as state officials and public role models. Nevertheless, the duration of the obligation until the ex-wife remarries has the potential to place an excessive burden on male civil servant.